A study on body mass index and menstrual cycle length in reproductive age women - Vashishta, Shilpi; Gahlot, Sushila (International Journal of Advances in Medicine, 2022)
Background: Menstrual cycle length is an indicator of reproductive health of a woman. Duration of menstrual cycle in a woman is affected by a number of factors including BMI. The effect of BMI on menstrual cycle length has been studied less extensively. Not many studies have been conducted on Indian populations. This study was conducted to study the relation of body mass index and menstrual cycle length in reproductive age women. Methods: The study included 225 women of age 15-45 years. Women with average menstrual cycle length of 24-38 were regarded as regularly menstruating women. Menstrual cycle length was defined as short (<24 days), normal (24-38 days), long (>38 days). During the menstrual phase of the cycle BMI of each participant was recorded. Results: A significant (p=0.0008) increase in mean BMI was found with increased in length of menstrual cycle. The majority of the women with long menstrual cycle were obese compared to women having normal and short length of menstrual cycle. Conclusions: The results of present study indicates that women with long menstrual cycle have increased body mass index compared to women having normal or short menstrual cycle length.